Interleaved cuk converter with improved transient performance and reduced current ripple. Issue 7 (24th July 2017) - K.D, Joseph; Daniel, Asha Elizabeth; Unnikrishnan, A.
Abstract : Boost DC–DC converters are widely used in non‐conventional power conversions namely in solar and wind power generation systems. It is also used in switched mode power supplies. Since there is no filter inductor on output side, output current of boost converter is pulsed and it is not desirable. The quality of power required is very high when DC–DC converters are employed for transferring the requisite amount of power. In this study, the conventional cuk converter (CCC) having a continuous current at both input and output sides is taken as the candidate for performance analysis. Accordingly an interleaved cuk converter (ICC) is proposed and designed to reduce the input current ripple and also to improve transient performances. Both the CCC and the proposed ICC are simulated and validated experimentally. The proposed converter is having better efficiency attributable to cancellation of source current ripple, reduction of ripple content in both output voltage and current, and improvement of transient performance.